2022
DOI: 10.1111/ggi.14424
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of muscle mass assessed by dual‐energy X‐ray absorptiometry and bioelectrical impedance analysis in older patients with heart failure

Abstract: Aim This study aimed to compare bioelectrical impedance analysis (BIA) and dual‐energy X‐ray absorptiometry (DEXA) in measuring skeletal muscle mass (MM), and its prognostic implications in old patients with heart failure. Methods We prospectively evaluated MM measured by both BIA and DEXA in 226 hospitalized elderly (≥65 years) patients with heart failure. The cut‐off values proposed by the Asian Working Group in Sarcopenia were used to define low MM. The prognostic endpoint was all‐cause death. Results The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Moreover, we have already reported from FRAGILE‐HF that sarcopenia assessed using BIA was independently associated with 1 year mortality, irrespective of left ventricular ejection fraction 7 . However, no study has reported an association between sarcopenia defined using DEXA and prognosis, although DEXA may be superior to BIA in terms of its prognostic value in patients with heart failure 10 . The current study is the first to show that sarcopenia diagnosed using DEXA is independently associated with all‐cause mortality.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Moreover, we have already reported from FRAGILE‐HF that sarcopenia assessed using BIA was independently associated with 1 year mortality, irrespective of left ventricular ejection fraction 7 . However, no study has reported an association between sarcopenia defined using DEXA and prognosis, although DEXA may be superior to BIA in terms of its prognostic value in patients with heart failure 10 . The current study is the first to show that sarcopenia diagnosed using DEXA is independently associated with all‐cause mortality.…”
Section: Discussionmentioning
confidence: 54%
“… 7 However, no study has reported an association between sarcopenia defined using DEXA and prognosis, although DEXA may be superior to BIA in terms of its prognostic value in patients with heart failure. 10 The current study is the first to show that sarcopenia diagnosed using DEXA is independently associated with all‐cause mortality.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations